Morfofisiologia do dossel e desempenho de ovinos em capim-tifton 85 - Bezerra, Ana Patrícia Almeida (2011)
The aim of the study was to evaluate morphophysiological characteristics of forage and sheep performance on Tifton 85 Bermudagrass. Three periods of rest were used with 4.5, 6.5 and 8.5 new leaves per tiller after stocking. The residual condition to delimited the end of stocking was forage height of 5 and 10 cm. It was used a completely randomized design arranged in a 3x2 fatorial scheme, with four replicates and two post-grazing periods (5 and 10 cm). Data of effect of periods of rest (PR) and post-grazing (PG) periods were initially analyzed and then the effect of continually grazing cycles. It was used the intermittent stocking grazing method, with variable stocking. A total of 30 Santa Ines sheep and variable number of regulating animals, with 20 kg of body weight, were distributed in groups of 5 animals among 6 treatments. At evaluation of initial growth, an increase of green culm dry matter maybe related to the increase of leaves area index throughout the evaluation and being responsible to reduce the green blade dry matter. Reductions in the values of relative growth rate, net assimilation and leaves area ratio with increasing the age of regrowth were observed. The rate of forage accumulation increased throughout the evaluation. Reductions were observed in tiller density and number of green leaves. The morphogenetic characteristics were affected by periods of rest (PR) and post-grazing residue (PG) and the effect of grazing cycles. Unnecessary higher PR to formation 6.5 leaves/tiller became morphogenical characteristics undesirable. The components of biomass in pre and post-grazing were affected by the interaction between PR x PG and the grazing season. The extension of the PR affect the forage structure. The use of Tifton 85 Bermudagrass should not exceed the PR of 6,5 leaves/tiller to avoid loss of forage due to senescence, using a residual height of 5 cm without compromising the sustainability of the pasture. The crude protein (CP) of both fractions was reduced with increasing PR. The coefficients of DIVMS of leaves fraction were adequate. It was observed that the variation of DIVMS of culm fraction of pastures grazed under three PR and two PR had low magnitude. Grazing cycles affected the chemical composition and DIVMS of two fractions. The pastures grazed under PR of 8,5 leaves/tiller and residue of 10 cm provided higher grazing time and ruminating. The 4th day of grazing provided more time of grazing and ruminating. The salt and water intakes were reduced. The highest bite rate was found in pastures under PD of 4,5 leaves/tiller. The 4th day of grazing provided an increase int the rate and number of bites and reduction at mass bite. PR corresponding to 4.5 and 6.5 leaves/tiller provided better performance. The higher support capacity, in animal units, was observed to pastures grazed under PD of 8.5 leaves/tiller. The higher dry matter intake was recorded at the 1st day of grazing. The management strategies affect carcass characteristics. The PD of 8.5 leaves/tiller was responsible for the greater weight of skin. The PR showed higher biological yield. The cuts were not affected by management strategies. The levels of humidity and lipids were affected by PR.